Letters from the Continent 1858 - Ruskin, John, 1819-1900 (Book collections on Project MUSE., 1982)
"By John Ruskin's own account, 1858 was a turning-point in his life--the year in which he turned away from his evangelical upbringing toward a more humanistic attitude. The 132 letters included in this volume were written during Ruskin's four-month tour of France, Switzerland, and Northern Italy and all but eleven are addressed to his father to whom he wrote almost daily, intending that the letters would form his diary. They provide not only a detailed record of his experiences at this significant point in his life, but also a revealing glimpse of his social and political awareness in his comments on current affairs. His delight in the physical pleasures of life in Turin, where he stayed for six weeks, reveals a different aspect of his developing humanistic concern. More than anything else, however, these letters illuminate Ruskin's relationship with his father. The speed with which letters passed between them permitted an exchange of attitudes and ideas impossible in their earlier correspondence. The letters reveal that the disagreement on political and social issues that was later to affect their relationship had not yet occurred--though the possibility of dissension is present in the intensity of feeling displayed by the elder Ruskin for his son. (Passages from John James Ruskin's letters are included in the notes.) They also reveal Ruskin's concern with the drawings he made on this tour, a number of which are reproduced in this volume"--Jacket